Pengaruh Kedalaman Pemakanan dan Kecepatan Potong pada Pembubutan Finishing Material Baja SKD 11 terhadap Kekasaran Permukaan Benda Bubutan - Restu, Ilham; Kurniawan, Zaldy; Erwansyah, Erwansyah (Politeknik Manufaktur Negeri Bangka Belitung, 2024)
One important factor in achieving good quality value for a product in the machining process is to look at the level of roughness produced in the machining process. This research aims to determine the effect of feed depth and cutting speed on surface roughness. The process variables used in this research are feeding depth (mm) and cutting speed (m/min). Each variable has 3 levels, namely feeding depth of 0.5, 0.6 and 0.7 mm. Cutting speed 65, 70 and 75 m/min. In this research method, researchers used the full factorial method. The material used in this research is SKD 11 steel. The conclusion obtained from the research is that the minimum surface roughness is at a cutting depth of 0.6 mm with a cutting speed of 65 m/minute, with the average surface roughness value obtained being 0.883 (µm ). The maximum surface roughness is at a feed depth of 0.6 mm with a cutting speed of 70 m/minute with an average surface roughness value of 1.254 (µm).